The ‘digital natives’ debate: A critical review of the evidence - Bennett, Sue; Maton, Karl; Kervin, Lisa (British Journal of Educational Technology, 2008)
The idea that a new generation of students is entering the education system has excited recent attention among educators and education commentators. Termed ‘digital natives’ or the ‘Net generation’, these...